Peningkatan Kemampuan Bahasa Pada Anak Usia 5-6 Tahun Melalui Media Pop Up Book: Peningkatan Kemampuan Bahasa Pada Anak Usia 5-6 Tahun Melalui Media Pop Up Book - Zuhra, Nurliza; Chairullah,; Aulia Rahmi , (Jurnal Serambi Ilmu, 2026)
Early childhood education is the most basic thing. One of the supports for the early childhood learning process to take place effectively is to use learning media. Based on the results of observations, the cause of the lack of children's language development in Mutiara Pelangi Kindergarten is due to the lack of provision of children's language stimulation. The formulation of the problem is how to implement and effectiveness along with obstacles in the application of pop up book media to improve children's language skills in Mutiara Pelangi Kindergarten. The purpose of this study is to find out how the application, effectiveness and obstacles in applying pop up book media in improving children's language skills in Mutiara Pelangi Kindergarten. This research method uses a qualitative descriptive approach, with a qualitative research type using purposiv sampling techniques. The result of this study is that the pop up book learning media can improve the aspect of children's language development in group B and this pop up book media is very interesting for children, this can be seen when the teacher tells stories using the pop up book media the children focus on paying attention to the teacher and the pop up book, and after the teacher finishes telling the story the children are very active in asking questions, convey their ideas and ideas.